KUMPULAN DASA WISMA DAN SETU LEGI SEBAGAI MODAL SOSIAL DI DUSUN BRAJAN - Nugrahani, Tri Siwi; Umam, M Sulkhanul (Universitas PGRI Yogyakarta, 2020)
The success of village development planning accompanied by community empowerment will improve the economy of the community in the region, which in turn can reduce economic inequality. Rural development is inseparable from the role of village communities as one of social capital. Dasa Wisma and Setu Legi Association is a place for social capital and community empowerment to improve the group's economy. However, as the economic drivers of the Brajan hamlet community in Potorono Village, the group experienced problems about the lack of orderliness of members because there were no written regulations and the absence of financial reports as a measurement of group assets. So that assistance to improve administration as a group's financial accountability and SOP for lending is absolutely necessary. The results of community service activities indicate that with the formulation of SOPs, it is expected that the lending mechanism will be obeyed by members and the borrower will be orderly in installments, as well as by preparing the group's financial statements, the assets owned can be identified. So that the group's financial development can be seen and allocated for more productive needs.